Nigeria : Background Papers and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Background Paper and Statistical Appendix examines economic development in Nigeria in the first half of the 1990s. Economic growth slowed for the fourth consecutive year in 1994, to 1.3 percent from 2.3 percent in 1993. The slowdown was widespread, affecting every sector except agriculture. Output in the petroleum sector is estimated to have declined by 6 percent, mainly as a result of industrial actions by oil workers during July and August 1994. In the non-oil sectors, negative growth was recorded in both fishing and manufacturing activities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet